POTENSI ANTIOKSIDAN INFUSA BUNGA TELANG (Clitoria ternatea), ROSELLA (Hibiscus sabdariffa) DAN DAUN STEVIA (Stevia rebaudiana) SEBAGAI ANTIDIABETES - Melania Perwitasari; Sinta Nuriyah Awaliyah; Intan Kurnia Putri; Nofria Rizki Amalia Harahap; Ariska Deffy Anggarany; Reza Anindita; Maya Uzia Beandrade; Dede Dwi Nathalia (Jurnal Mitra Kesehatan, 2023)
Reactive Oxygen Species (ROS) can induce oxidation that caused aging and degenerative diseases such as Diabetic Mellitus. To prevent the incident of degenerative disease, antioxidant needed that found in many herbs, especially colored herbs. Butterfly pea, Rosella flower, and Stevia leaf known as herbs contains phenolic and flavonoid. This constituent are responsible as antioxidant activity. Many people consume the herbs by brewing with hot water as infused water. The purpose of this research is to determine antioxidant activity of infused Butterfly pea, Rosella flower, and Stevia leaf by FRAP method. This is non experiment method descriptive with dry herbs of Butterfly pea, Rosella flower, and Stevia leaf infused extract as sample. The research was conducted in September 2022-February 2023 at STIKes Mitra Keluarga Laboratory. The antioxidant activity is expressed as % FRAP activity. Based on the experiment, it knows that % FRAP activity of Butterfly pea, Rosella flower, and Stevia leaf consecutive 55,29% ± 0,0, 69,17% ± 0,12 , 61,55% ± 0,04.